The Uncertainty Surrounding the Government's Pronouncements on the COVID-19 Situation - Iskandarsyah Siregar (Budapest International Research and Critics University, 2023)
In this comprehensive research, we delve into an analytical examination of the official statements made by the government concerning the COVID-19 pandemic situation. The primary objective of this investigation is to decipher and understand the nuances of the government's communication to ensure that the general populace is not misinformed or led astray by any ambiguities present in these statements. To lay a theoretical foundation for this analysis, we have employed the principles of semantic studies, which provide valuable insights into the meanings and interpretations of words and sentences.Given the nature of our research, a descriptive methodology has been chosen. This approach is deemed most appropriate because it offers a detailed representation of the collected data. To gather this data, extensive observations were conducted, specifically focusing on the portrayal of government declarations in various mass media outlets. By scrutinizing these pronouncements, we aim to shed light on areas where the government's messaging might be unclear or open to various interpretations.The culmination of this research presents an elucidative account, highlighting the instances and specific terminologies where the government's communication appears ambiguous. This ambiguity, whether intentional or accidental, has the potential to impact public understanding, especially concerning the pressing matter of the COVID-19 pandemic. Our findings underscore the need for precise, clear, and unequivocal communication, particularly in matters of public health and safety.